2011
DOI: 10.1007/s12665-011-1108-7
|View full text |Cite
|
Sign up to set email alerts
|

Hydrochemical and hydrological processes in the different landscape zones of alpine cold region in China

Abstract: Investigation of water sources and flow pathways is crucial to understand and evaluate the characteristics of surface water and groundwater systems. This article aims to identify the hydrochemical and hydrological processes in different landscape zones based on hydrochemical analyses of various samples, including samples from glacier, snow, frozen soil meltwater, surface water, groundwater, and precipitation, in the alpine cold region of China. Hydrochemical tracers indicated that chemical compositions are cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…Isotopic tracers can provide valuable information on complex hydrological problems, such as the runoff processes, residence time, runoff pathway and the origin and contribution of each runoff component (Arny et al, 2013;Ohlanders et al, 2013;Yang et al, 2012a;McInerney et al, 2011;Maurya et al, 2011;Kevin et al, 2010). The isotopes of D and 18 O are conservative and do not react with clay minerals and other soil materials.…”
Section: Introductionmentioning
confidence: 99%
“…Isotopic tracers can provide valuable information on complex hydrological problems, such as the runoff processes, residence time, runoff pathway and the origin and contribution of each runoff component (Arny et al, 2013;Ohlanders et al, 2013;Yang et al, 2012a;McInerney et al, 2011;Maurya et al, 2011;Kevin et al, 2010). The isotopes of D and 18 O are conservative and do not react with clay minerals and other soil materials.…”
Section: Introductionmentioning
confidence: 99%
“…The isotopic composition of river water was low due to recharge by glacier snow meltwater and thawed frozen soil. It is revealed that river water is recharged by thawed frozen soil, glacier snow meltwater and precipitation in the wet season [3,9,38]. During the dry season, in river water in the lower reaches, δ 18 O ranges from −8.91‰ to −8.84‰, and δD ranges from −52.46‰ to −51.72‰, respectively, between groundwater and meltwater, which indicates that river water is recharged by groundwater and meltwater.…”
Section: Temporal and Spatial Variations Of Runoff Processmentioning
confidence: 96%
“…The lithology is dominated by Paleozoic-Mesozoic and Cenozoic sandstone, conglomerate, shale, limestone and slate, which have degenerated to different degrees [3,9,39]. There is abundant bedrock fissure water, which is characterized by metamorphic and clastic rock dating from the Paleozoic to the Cenozoic [3,9,40].…”
Section: Hydrogeological Backgroundmentioning
confidence: 99%
See 2 more Smart Citations